2003
DOI: 10.1177/0890334403252537
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Breastfeeding in Swedish Primiparous and Multiparous Women

Abstract: The aim of this study was to describe the effects of sociodemographic factors and maternity ward practices on the duration of breastfeeding in Swedish primiparas (n = 194) and multiparas (n = 294), consecutively selected from hospital birth files for 3 months, who responded to a questionnaire 9 to 12 months after childbirth. The impact of sociodemographic data and maternity ward practices on exclusive and any breastfeeding were examined. Smoking and supplementation without medical reasons influenced the durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 24 publications
(23 reference statements)
5
81
1
10
Order By: Relevance
“…Similar results were obtained in study done by Agre et al and Holmes et al [15][16][17] However, Ekström et al concluded that parity had no significant influence. 18 Haroon et al concluded that both individual and group counseling markedly increases exclusive breast-feeding rates. 19 A meta-analysis of 53 studies, has demonstrated that prenatal and postnatal counseling increased EBF rates manifold.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in study done by Agre et al and Holmes et al [15][16][17] However, Ekström et al concluded that parity had no significant influence. 18 Haroon et al concluded that both individual and group counseling markedly increases exclusive breast-feeding rates. 19 A meta-analysis of 53 studies, has demonstrated that prenatal and postnatal counseling increased EBF rates manifold.…”
Section: Discussionmentioning
confidence: 99%
“…L'effet de la longueur du séjour à l'hôpital n'est pas clair. Deux études suédoises ont obtenu des résultats contradictoires : l'une montrant que la longueur du séjour hospitalier après la naissance n'était pas associée avec la durée de l'allaitement et que certaines caractéristiques maternelles pouvaient être des prédicteurs plus importants d'un allaitement prolongé [36] ; l'autre montrant qu'une sortie « rapide » de l'hôpital (72 heures après la naissance) était associée à une durée plus courte d'allaitement maternel exclusif [37].…”
Section: Facteurs Liés à L'accouchementunclassified
“…Les mères rapportent un manque d'encouragements individualisés de la part de leur médecin dans la période qui suit directement la sortie de l'hôpital [44], ou bien elles reçoi-vent un soutien qui n'est pas toujours positif, étant donné les connaissances obsolètes des soignants et leur manque d'intérêt concernant l'allaitement maternel [37]. Un soutien considéré comme faible par les mères est associé à un taux élevé d'arrêt de l'allaitement avant trois mois, tandis que les mères qui reçoivent des informations répétées allaitent plus longtemps [15].…”
Section: Soutien Des Professionnels De Santéunclassified
“…In addition, results from the baseline study did not show any significant differences in the women's perceived support in childbearing and breastfeeding, from the professional in the municipalities involved in the study [35,36].The paired municipalities were randomly designated to intervention (five municipalities) or control (five municipalities) by a person not involved in the study. The randomization was done before any data collection began.…”
Section: Phase 1: Randomization and The Process-oriented Training Promentioning
confidence: 99%
“…Based on the findings of a baseline study [35,36], the 10 largest municipalities in the selected area were grouped into pairs according to their size and the duration of breastfeeding in those municipalities. In addition, results from the baseline study did not show any significant differences in the women's perceived support in childbearing and breastfeeding, from the professional in the municipalities involved in the study [35,36].The paired municipalities were randomly designated to intervention (five municipalities) or control (five municipalities) by a person not involved in the study.…”
Section: Phase 1: Randomization and The Process-oriented Training Promentioning
confidence: 99%